Ionic fluids containing both strongly and weakly interacting ions of the same charge have unique ionic and chemical environments as a function of ion concentration - Wang, Hui; Kelley, Steven P.; Brantley, Jimmy W.; Chatel, Gregory; Shamshina, Julia; Pereira, Jorge F. B. [UNESP]; Debbeti, Varun; Myerson, Allan S.; Rogers, Robin D. (Wiley, 2015)
Liquid multi-ion systems made by combining two or more salts can exhibit charge ordering and interactions not found in the parent salts, leading to new sets of properties. This is investigated herein by examining a liquid comprised of a single cation, 1-ethyl-3-methylimidazolium ([C2mim]+), and two anions with different properties, acetate ([OAc]-) and bis(trifluoromethylsulfonyl)imide ([NTf2]-). NMR and IR spectroscopy indicate that the electrostatic interactions are quite different from those in either [C2mim][OAc] or [C2mim][NTf2]. This is attributed to the ability of [OAc]- to form complexes with the [C2mim]+ ions at greater than 1:1 stoichiometries by drawing [C2mim]+ ions away from the less basic [NTf2]- ions. Solubility studies with molecular solvents (ethyl acetate, water) and pharmaceuticals (ibuprofen, diphenhydramine) show nonlinear trends as a function of ion content, which suggests that solubility can be tuned through changes in the ionic compositions.
Keywords: concentration effects; ionic liquids; IR spectroscopy; NMR spectroscopy; solvent effects